Marketing Mix Implementation Strategy in Improving Teacher Performance: A Study at State Senior High Schools In Bandung City - Sinaga, Herty Ramayanti (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2024)
This study examines the impact of marketing mix elements (Product, Price, Promotion, Place) on teacher performance in Bandung City’s State Senior High Schools. Using quantitative methods and multiple regression analysis, the findings reveal that Product and Place have the strongest positive influence, while Price moderately contributes, and Promotion shows limited direct impact. Validity, reliability, and normality tests confirm robust data quality. The results emphasize the importance of curriculum innovation, equitable incentives, and quality infrastructure in enhancing teacher performance. Recommendations for holistic improvements in education management are discussed.